Delayed neurodegeneration and early astrogliosis after excitotoxicity to the aged brain - Castillo-Ruiz, M.M.; Campuzano, O.; Acarin, L.; Castellano, B.; Gonzalez, B. (Experimental gerontology, 2007)
Excitotoxicity is well recognised as a mechanism underlying neuronal cell death in several brain injuries. To investigate age-dependent differences in neurodegeneration, edema formation and astrogliosis, intrastriatal N-methyl- d-aspartate injections were performed in young (3 months) and aged (22–24 months) male Wistar rats. Animals were sacrificed at different times between 12 h and 14 days post-lesion (DPL) and cryostat sections were processed for Toluidine blue, Fluoro-Jade B staining, NeuN and GFAP immunohistochemistry. Our results show that both size of tissue injury and edema were reduced in the old subjects only up to 1DPL, correlating with a slower progression of neurodegeneration with peak numbers of degenerating neurons at 3DPL in the aged, contrasting with maximum neurodegeneration at 1DPL in the young. However, old animals showed an earlier onset of astroglial response, seen at 1DPL, and a larger area of astrogliosis at all time-points studied, including a greater glial scar. In conclusion, after excitotoxic striatal damage, progression of neurodegeneration is delayed in the aged but the astroglial response is earlier and exacerbated. Our results emphasize the importance of using aged animals and several survival times for the study of acute age-related brain insults.